Environmental performance evaluation of gasoline supply chain in Indonesia: A life cycle assessment (LCA) approach - Kurniawan, Bobby; Salsabila, Farah; Irman, Ade (Journal Industrial Servicess, 2024)
Environmental performance serves as a measure of a company’s responsibility toward the environment. Corporate environmental responsibility encompasses a broad range of areas, extending beyond the company’s immediate territory. Environmental damage that threatens ecosystems is primarily caused by pollution and degradation, especially within the oil and gas industry. This study investigates the environmental effects of a fuel terminal in distributing fuel to customers. A fuel distribution terminal produces four categories of environmental impacts: global warming, ozone layer depletion, acid rain, and eutrophication. The potential impact of global warming, based on three process units, is 117,664,330 kilograms of carbon dioxide equivalent (CO2 Eq.). The potential impact of ozone depletion, also based on three process units, is 274.84715 kilograms of chlorofluorocarbon-11 equivalent (CFC-11 Eq.). The potential impact of acid rain, based on three process units, is 169,227.85 kilograms of sulfur dioxide equivalent (SO2 Eq.). Lastly, the potential impact of eutrophication, based on three process units, is 259,521.64 kilograms of phosphate equivalent (PO4 Eq.).